2021
DOI: 10.1182/bloodadvances.2021004288
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities are risk factors for hospitalization and serious COVID-19 illness in children and adults with sickle cell disease

Abstract: Patients with sickle cell disease (SCD) are at high risk of developing serious infections, therefore, understanding the impact that severe acute respiratory syndrome coronavirus 2 infection has on this population is important. We sought to identify factors associated with hospitalization and serious COVID-19 illness in children and adults with SCD.We established the international SECURE-SCD Registry to collect data on patients with SCD and COVID-19 illness. We used multivariable logistic models to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 26 publications
4
88
3
2
Order By: Relevance
“…Up-regulation of ACE-2 expression in COPD, and delayed innate antiviral immune response in asthma (45) are mechanisms that possibly explain the higher risk of severe COVID-19 infection and mortality among those with respiratory comorbidities (40). Several studies have found that SCD patients with heart and lung comorbidities were at higher risk of severe COVID-19 infections (46,47). Similarly, the mortality rate among thalassemia patients with cardiovascular comorbidities was significantly higher when compared to its counterpart without underlying cardiovascular disease (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of ACE-2 expression in COPD, and delayed innate antiviral immune response in asthma (45) are mechanisms that possibly explain the higher risk of severe COVID-19 infection and mortality among those with respiratory comorbidities (40). Several studies have found that SCD patients with heart and lung comorbidities were at higher risk of severe COVID-19 infections (46,47). Similarly, the mortality rate among thalassemia patients with cardiovascular comorbidities was significantly higher when compared to its counterpart without underlying cardiovascular disease (48).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that SCD patients with heart and lung comorbidities were at higher risk of severe COVID-19 infections ( 46 , 47 ). Similarly, the mortality rate among thalassemia patients with cardiovascular comorbidities was significantly higher when compared to its counterpart without underlying cardiovascular disease ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to risk factors for COVID-19 related severity, the only variable that held up to MVA for the outcome of hospitalization was admission Hb; this is consistent with previous findings of a significant Hb decrease from baseline for SCD patients requiring hospitalization [1] and studies that reported Hb as a strong predictor of COVID-19 related severity or mortality in the general population [16] , [24] , [25] For the outcome of ICU admission, 3 variables remained significant in the MVA: HCW employment, HU use, and immature granulocyte count on admission. HCW employment has not been previously reported as a risk factor in SCD ICU admission but has been associated with COVID-19 morbidity in the general US population as well as comprehensive meta-analysis [13] , [14] .. HU use has been reported to reduce morbidity in SCD in one report [1] but not others [10] , [21] . It is biologically plausible that HU might decrease morbidity from COVID-19 infection due to reduction of coagulation and neutrophil and endothelial cell activation [26] , [27] , [28] .…”
Section: Discussionmentioning
confidence: 92%
“…Since COVID-19 infection may precipitate or exacerbate SCD-related complications [8] , [10] , [21] , complications were classified as SCD-related or COVID-19-related as per Table 2 ; outpatients had no complications. Of the 15% (4 of 27) adults who experienced COVID-19 complications, all went to the ICU and required intubation, whereas no children had COVID-19 related complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation